2014
DOI: 10.2147/ijwh.s43591
|View full text |Cite
|
Sign up to set email alerts
|

Embolization of uterine fibroids from the point of view of the gynecologist: pros and cons

Abstract: Uterine artery embolization (UAE) is a minimally invasive procedure with large symptomatic potential in treatment of women with uterine leiomyomas. Due to specificities of this method and possible complications the appropriate indication is crucial. Patient’ symptoms, age, plans for pregnancy, and surgical and reproductive history play a major role in decision-making regarding appropriate subjects for UAE. Close cooperation between the gynecologist and the interventional radiologist is necessary. UAE is usuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 66 publications
0
18
0
3
Order By: Relevance
“…Meddőség, ismételt vetélés kapcsán elvégzett beavatkozásokkal is találkozhatunk az irodalomban, illetve leírnak embolisatio után fogant és kihordott terhességet is [36]. Hosszú távú szövődményként a korai petefé-szek-kimerülés, infekció, amely későbbi petevezetőfunk-ció-vesztéssel meddőséghez vezethet, terhesség alatti méhruptura, illetve a placenta keringésének zavara figyelhető meg [37].…”
Section: Radioterápiaunclassified
“…Meddőség, ismételt vetélés kapcsán elvégzett beavatkozásokkal is találkozhatunk az irodalomban, illetve leírnak embolisatio után fogant és kihordott terhességet is [36]. Hosszú távú szövődményként a korai petefé-szek-kimerülés, infekció, amely későbbi petevezetőfunk-ció-vesztéssel meddőséghez vezethet, terhesség alatti méhruptura, illetve a placenta keringésének zavara figyelhető meg [37].…”
Section: Radioterápiaunclassified
“…Although UAE is highly effective in reducing bleeding and the size of the myoma, it may be necessary to repeat the procedure in 15-20% of cases after successful embolization, and in up to 50% of cases of incomplete ischemia. 16,17 (C,D) There are also concerns about the impact of UAE on the ovarian reserve. 18 (C) The desire for future gestation is still recognized as a relative contraindication because there are not enough studies in the literature to guarantee good results.…”
Section: (C)mentioning
confidence: 99%
“…Hysterectomy remains the most frequent surgical procedure to treat uterine fibroids among women who develop severe symptoms during their childbearing years [ 2 , 7 , 8 , 9 , 10 , 11 ]. A study of patient data for the period of 1998 to 2010 indicated that 7,438,452 inpatient hysterectomies were performed in the United States [ 12 , 13 ], 40% of which were to treat patients for uterine fibroids. In 2001 through 2003, women who had abdominal hysterectomy had a longer length of stay [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is considerable anxiety among women about losing their uteri. Thus, many would prefer alternative procedures to remove the fibroid, saving the uterus, relieving them of the pain, and providing a sense of relief [ 6 , 12 , 16 , 17 , 18 , 19 ]. In addition, better quality of life outcomes have been correlated with these alternative procedures [ 6 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%